The Evaluation of Barbell Trajectory in Accordance with coincident Amended Lines with the Movement of feet in Snatch Lift. - Laith .A. A L- Obayde (مجلة الرافدين للعلوم الرياضية, 2011)
Abstract Researches had been directed towards the barbell trajectory of the weight as an indicator to the performance and actual expression to the range of weight lifter biomechanical capabilities. Several studies have been conducted on snatch lift; they almost depended on the amendments done by (Roman & Chakirzenove) in treating jump issue among weight lifters predominantly forward and backward. This were studied by using the amount of total jump distance according to the direction of jump in deviation variables (D2-D3-D4-D5-D6), as the distance during the jump has never been passed usually by the weight lifters, the researcher sought to measure the actual distance on each variable and amended the values of weight deviations (D2-D3-D4-D5-D6), the error measurement may be well-deserved to reach to the real values of these deviations. The current paper aimed to: 1. Identify the values of weight deviations in snatch lift by two methods of (Roman and Shakirzenove) for the amended line of jump issues and the proposed method. 2. Identify the differences in weight deviations in snatch lift between the two methods of (Roman and Shakirzenove) and the proposed one to the amended line for the jump issues. 3. Identify the values and differences in jump distance between the two methods of (Roman & Chakirzenove) and the proposed method. 4. Identify the relative change of weight deviations in snatch lift (Roman & Chakirzenove) and the proposed method of amended line of jump issues. The researcher proposed that: 1. There are significant differences in values of some weight deviations and the jump distance in snatch lift between two methods of (Roman and Shakirzenove) and the proposed method to the amended line for the jump issues. 2. There is variance differences of relative change in the values of weight deviations in snatch lift between (Roman & Chakirzenove) and the proposed method of amended line of jump issues. Materials and Methods included: - Human Resources: Weight lifters training camp participated and Asia Championship Nominated in Uzbekistan Youth. - Time Resources: 3.4.2010 – 3.11.2011. - Spatial resources: Youth Center – Al-Kufa (Najajaf). The descriptive method were accounted in this paper, the sample were (10) weight lifters and participants in country championship, the researcher used technical scientific observations, data analysis and data collection to reach to the variables of weight deviations. In order to achieve the technical scientific observations, video camera (Sony) were used, and fixed ( 4.m distance) on the right hand of weight lifter. The lens of camera were 1m height on the level students, the capture velocity were (25) pix/sec. The trials of payer’s tape recorder were computerized. Data were analyzed technically and statistically: Film Adobe Image Ready (v8)-Adobe Photo shop (v8) – Excel –Word Processing. The data were statistically treated by Mean Value, Deviation Regression, Percentage, Variance Rate, t – test, and SPSS. The researcher recommended: 1. There are significant differences in values of jump distance values to measure the maximum deviation of weight far from the weight lifter for the difference between the (Roman & Chakirzenove) and the proposed method. 2. The proposed method has been named (Laith Al-Obaidi) to save the intellectual property.